Somatic Mutation Profiles Revealed by Next Generation Sequencing (NGS) in 39 Chinese Hepatocellular Carcinoma Patients - Ke, Lixin; Shen, Jianming; Feng, Jikun; Chen, Jialin; Shen, Shunli; Li, Shaoqiang; Kuang, Ming; Liang, Lijian; Lu, Cuncun; Li, Dongming; He, Qiang; Peng, Baogang; et al. (Frontiers in Molecular Biosciences, 2022)
The features and significance of somatic mutation profiles in hepatocellular carcinoma (HCC) have not been completely elucidated to date. In this study, 39 tumor specimens from HCC patients were collected for gene variation analysis by next-generation sequencing (NGS), and a correlation analysis between mutated genes and clinical characteristics was also conducted. The results were compared with genome data from cBioPortal database. Our study found that T > G/A > C transversions (Tv) and C > T/G > A transitions (Ti) were dominant. The sequence variations of TP53, MUC16, MUC12, MUC4 and others, and the copy number variations (CNVs) of FGF3, TERT, and SOX2 were found to be more frequent in our cohort than in cBioPortal datasets, and they were highly enriched in pathways in cancer and participated in complex biological regulatory processes. The TP53 mutation was the key mutation (76.9%, 30/39), and the most common amino acid alteration and mutation types were p.R249S (23.5%) and missense mutation (82.3%) in the TP53 variation. Furthermore, TP53 had more co-mutations with MUC17, NBPF10, and AHNAK2. However, there were no significant differences in clinical characteristics between HCC patients with mutant TP53 and wild-type TP53, and the overall survival rate between treatment via precision medication guided by NGS and that via empirical medication (logrank p = 0.181). Therefore, the role of NGS in the guidance of personalized targeted therapy, solely based on NGS, may be limited. Multi-center, large sample, prospective studies are needed to further verify these results.